Masculine and metrosexual: Indonesian actor’s clothing style on Instagram from the Foucauldian perspective - Teguh Dwi Putranto; Rahma Sugihartati; Santi Isnaini; Suko Widodo (SIMULACRA: JURNAL SOSIOLOGI, 2020)
This study seeks to explore the fashion styles of Indonesian actors on Instagram from Foucault’s perspective. Appearance is a demand that is not only aimed at women but also for men. Appearance is an important part, especially for men, so that also increases the metrosexual side. The enhancement of men’s appearance in clothing has increased metrosexuality. The metrosexual side has been viewed by society as indicating the waning masculine side of a man. Thus, some people believe that metrosexual men lose their identity entirely because excessive attention to appearance is associated with women identity. The method used in this study was the Krippendorff content analysis carried out on Joe Taslim’s Instagram account Instagram posts from October 2019 to February 2020. Joe Taslim, known as an Indonesian action actor, is a figure with a masculine appearance chosen in this study to represent a masculine men figure but still looks metrosexual. The results of this study indicate that Joe Taslim’s Instagram is used as a medium in creating fantasies about the men body metrosexual, which is run by the capitalist industry to create a masculine impression.